The functions of external voices in hard news Appraisal: A dialogic perspective - Nádraská, Zuzana (de Gruyter Open, 2017)
This paper discusses the interaction between voices in the so-called Appraisal satellite, a section in the generic structure of hard news concerned with evaluation (White, 1998). The discussion focuses primarily on the interplay between external voices brought into the discourse by various forms of presentation, i.e. forms of reporting the language of others (Semino and Short, 2004); in addition, the paper touches upon the interplay between external voices and the internal authorial voice of the journalist. External voices are considered in terms of the function they fulfil in hard news Appraisal. Prototypically, external voices serve as the main source of evaluation but also fulfil various subsidiary roles; for instance, voices serve as the target of evaluation, express attitude, and provide a summary, background information and justification. Correspondences are found between voice functions and forms of presentation. Voice functions are interpreted from a dialogic perspective, more specifically in terms of their potential to expand and contract the established dialogic space (Martin and White, 2005).
Funkce externích hlasů v evaluativních částech novinové zprávy: Dialogická perspektiva
Keywords: hard news; Appraisal satellite; evaluation; forms of presentation; external and internal voice; voice function; dialogue; dialogic expansion and contraction; novinová zpráva; evaluace; evaluativní část žánrové struktury; externí a interní hlasy; funkce hlasu; dialog a vícehlasí